Bioinspired wafer-scale production of highly stretchable carbon films for transparent conductive electrodes - Li, Rongjin; Parvez, Khaled; Hinkel, Felix; Feng, Xinliang; Muellen, Klaus (Angewandte Chemie International Edition, 2013)
Carbon-based films: Dopamine was used as the precursor for the facile yet controllable production of a highly stretchable transparent conductive film (see picture). The film synthesized is transparent and can reversibly withstand mechanical deformations (such as being stretched to 20 % for 100cycles). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: carbon; carbon electrodes; dopamine; graphene; molecular devices